Methanolic extracts of Withania somnifera leaves, fruits and roots possess antioxidant properties and antibacterial activities - Alam Nadia; Hossain Monzur; Mottalib Md; Sulaiman Siti; Gan Siew; Khalil Md (BMC, 2012)
Abstract Background Withania somnifera, also known as ashwagandha, is an important herb in ayurvedic and indigenous medical systems. The present study was designed to evaluate the antioxidant and antibacterial activities of an 80% aqueous methanolic extract of W. somnifera roots (WSREt), fruits (WSFEt) and leaves (WSLEt). Methods Several assays were performed to determine the antioxidant properties of this herb including 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) scavenging activity, ferric reducing antioxidant power (FRAP), ferrous chelation and inhibition of β-carotene bleaching. Results The values for DPPH, FRAP, ferrous chelation and inhibition of β carotene bleaching for the three types of extracts ranged from 101.73-801.93 μg/ml, 2.26-3.29 mM Fe/kg, 0.22-0.65 mg/ml and 69.87-79.67%, respectively, indicating that W. somnifera, particularly the leaves, possesses significant antioxidant properties. The mean ascorbic acid content was 20.60-62.60 mg/100 g, and the mean anthocyanin content was 2.86-12.50 mg/100 g. Antibacterial activities were measured using the agar well diffusion method and five pathogenic Gram-negative bacteria: Escherichia coli, Salmonella typhi, Citrobacter freundii, Pseudomonas aeruginosa and Klebsiella pneumoniae. The leaf extracts displayed the highest activity against S. typhi (32.00 ± 0.75 mm zone of inhibition), whereas the lowest activity was against K. pneumoniae (19.00 ± 1.48 mm zone of inhibition). The lowest minimum inhibitory concentration value was 6.25 mg/ml, which was against S. typhi, followed by 12.5 mg/ml against E. coli. Conclusion In addition to its antioxidant properties, W. somnifera exhibited significant antibacterial activities against Gram-negative bacteria, particularly S. typhi.